Uprecycling leater waste - Santos, José dos Santos [UNESP]; Cabrera, Flávio Camargo [UNESP]; Agostini, Delber Lincon da Silva [UNESP]; Budemberg, Eduardo Roque [UNESP]; Job, Aldo Eloizo [UNESP] (My University, 2014)
Incorporating contaminated leather waste into natural rubber improves the rubber's mechanical properties and avoids improper disposal of toxins.